Determination of Enzymatic Antioxidant in Iraqi Patients with Chronic Gastritis - Wasan A. Bakir; Shalal M. Hussein; Noah A. Mahmood (College of Pharmacy University of Baghdad, 2017)
Infection of the gastric mucosa with Helicobacter pylori is strongly associated with chronic gastritis, peptic ulcer and gastric cancer. Helicobacter pylori virulence factors include a variety of proteins that are involved in its pathogenesis, such as VacA and CagA. Another group of virulence factors is clearly important for colonization of H.pylori in the gastric mucosa. These include urease, motility factors (flagellin), and Superoxide dismutase (SOD). Because of this organism's microaerophilic nature and the increased levels of reactive oxygen in the infected host, we expect that other factors involved in the response to oxidative stress are likely to be required for virulence. Superoxide dismutase is a nearly ubiquitous enzyme among organisms that are exposed to toxic environments. In this study, we measured the SOD in serum of 80 patients complain from chronic gastritis and infected with H.pylori. 37 patients infected with H.pylori have the CagA gene, and 13 patients are not and also measured the SOD in 30 control groups that not infected with H.pylori. Serum level of SOD was significantly (p<0.05) higher in patients with chronic gastritis compared to controls. Also significantly higher (p<0.001) in patients with chronic gastritis infected with H.pylori positive CagA than patients infected with H.pylori negative CagA. Key words: chronic gastritis, H.pylori, CagA, SOD Ø§Ù"Ø®Ù"Ø§ØµÙ€Ù€Ø©